Cardiology Research Institute, Tomsk National Research Medical Center - B. A. Tatarsky; N. V. Kazennova; R. E. Batalov; S. V. Popov (Российский кардиологический журнал, 2020)
Aim. To test the hypothesis that the combined use of ivabradine (If inhibitor) and ranolazine (late sodium channel blocker) can reduce the ventricular rate in patients with permanent atrial fibrillation (AF) resistant to standard heart rate-lowering therapy.Material and methods. The study included 25 patients with a permanent AF and an uncontrolled ventricular rate. All patients had NYHA class I-III heart failure with preserved ejection fraction. Patients took ivabradine 2,5 mg twice daily and ranolazine 250 mg twice daily. Twenty-four Holter monitoring was performed after 1, 2, 4 weeks and at the end of the study. The follow-up lasted 8 weeks.Results. In 68% and 16% of patients, strict and lenient rate control was achieved, respectively. There was no ventricular rate decrease in 12% of patients. Adverse effects developed in 4% of subjects.Conclusion. The combined use of ivabradine and ranolazine in patients with a permanent AF and uncontrolled ventricular rate reduces the rate without QT prolongation or reducing left ventricular contractile function. The findings support the hypothesis that the suppression of If current and dominant fibrillation frequency may be a new goal of permanent AF therapy. Prospective, randomized studies are needed to determine the role of drugs for ventricular rate control in patients with permanent AF and to study the effects on efficacy, safety, hospitalization frequency, and other clinical outcomes.